I was a rat! - Pullman, Philip, 1946-; Hawkes, Kevin (New York : Knopf : Distributed by Random House, 2000)
A little boy turns life in London upside down when he appears at the house of a lonely old couple and insists he was a rat.
Wilson's Children.
Wilson's Junior High School.
School Library Journal starred.
5.4
3-6
Keywords: Humorous stories; Humorous fiction; Humorous stories; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction